Pengaruh Personal Value Terhadap Perilaku Etis Mahasiswa Akuntansi - Adli Muzakki; Vanica Serly (Universitas Negeri Padang, 2023)
This study aims to provide an overview of the influence of personal values ​​on ethical behavior of accounting students. Sample of this study are the student of the economics faculty of Padang State University. Data was collected by survey using open ended questionnaire, an analyzed by simple linear regression technique The results of this study show that (1) Personal value-Openness to Change has no significant effect on ethical behavior of Accounting Student (2) Personal value-Self-Enhancement has a significant negative effect on ethical behavior of Accounting students (3) Personal value-Conservation has a significant positive effect on ethical behavior of Accounting Student (4) Personal value-Self-Transcendence has no significant effect on ethical behavior of Accounting Student.